Speed of word retrieval in multiple sclerosis - Khatoonabadi, Ahmad Reza (Medknow Publications & Media Pvt Ltd, 2013)
BACKGROUND: Multiple sclerosis (MS) is a common inflammatory - degenerative disease of myelin sheet of central nervous system that affects more young people. These patients show some degrees of cognition problems such as memory and processing disorders. The aim of this study was to evaluate the speed processing ability by word finding assessment in three categories include fruits, animals and objects in MS patients. MATERIALS AND METHODS: This study carried out as case-control and descriptive-analytic on 47 MS patients and 29 healthy controls. We measured the reaction time (RT) in three stages. Each stage includes 25 words (animals, fruits and objects words with high familiarity) that were presented randomly. In each stage, the subject should press a key when recognized the target category. Collected data analyzed with repeated measure ANOVA, two-way ANOVA test, and independent-samples t-test. RESULTS: MS patients in comparison to normal healthy subjects show delay in speed of processing in which there was significant difference between MS patients and control subjects in mean reaction time in all three categories (P < 0.001). CONCLUSION: The speed of processing is impaired in MS patients. Consequently, more evaluation and planning treatment programs based of speed processing for memory in these patients are necessary for them because of the role of memory in daily activities of life.